Creation of a sustainable model for building and maintaining a relationship between universities and entrepreneurs - Zunda, Santa; Zeps, Artūrs; Strode, Solvita (Business, Management and Economics Engineering, 2020)
Purpose – the article aims to analyse the best practices in industry-university collaboration and based on theoretical background and practical experiences of universities to provide a framework for building a sustainable industry-university collaboration model, which indicates processes and steps as well as an example of Riga Technical University on how to create and maintain such collaboration. Research question – how to structure the activities for setting up the collaboration with industry based on the desired collaboration intensity. Hypothesis – universities can effectively organise collaboration with industry if they understand what the specific achievable results they want to achieve are.Research methodology – based on literature analysis, best practice and problems analysis of universities and Riga Technical University case analysis of university-industry collaboration, a model for improving collaboration with industry is proposed.Findings – to establish an effective and productive university-industry collaboration university must apply a structured approach of communication and collaboration of all internal parties involved in the process, what can be done by using the SADI Model for Building a Relationship between Universities and Entrepreneurs. For successful implementation of the university’s strategy of collaboration with industry-university must define the achievable results for such collaboration and apply the SADI Model at the appropriate intensity level – basic, medium or high level.Research limitations – such a model hasn’t been fully implemented, so the full spectrum of all activities and their performance hasn’t been tested yet, as the implementation of it requires the involvement of multiple university departments. As well a limited approbation of the model is done since it is tested within Riga Technical University.Practical implications – the model can be used in different intensity levels according to the university’s strategical aims and desired achievable results from the collaboration with the industry. Originality/Value – the article supplements previous research done in the field of university-industry collaboration, providing an approach “SADI Model for Building a Relationship between Universities and Entrepreneurs” on how to structure and organise the collaboration with industry within the university as well as provides structured approach on how to define activities to be implemented by university based on the desired outcomes form such collaboration.